2008
DOI: 10.1017/s1461145708009206
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal immune activation leads to multiple changes in basal neurotransmitter levels in the adult brain: implications for brain disorders of neurodevelopmental origin such as schizophrenia

Abstract: Maternal infection during pregnancy enhances the offspring's risk for severe neuropsychiatric disorders in later life, including schizophrenia. Recent attempts to model this association in animals provided further experimental evidence for a causal relationship between in-utero immune challenge and the postnatal emergence of a wide spectrum of behavioural, pharmacological and neuroanatomical dysfunctions implicated in schizophrenia. However, it still remains unknown whether the prenatal infection-induced chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(160 citation statements)
references
References 72 publications
7
146
2
5
Order By: Relevance
“…Postmortem neurochemical analyses using high-performance liquid chromatography (HPLC) were performed as previously described (Enard et al, 2009;Winter et al, 2009). The levels of monoamines dopamine (DA) and serotonin (5-HT) and their metabolites dihydroxyphenylacetic acid (DOPAC), homovanillic acid (HVA), and 5-hydroxyindoleacetic acid (5-HIAA) in various brain areas were measured by HPLC with electrochemical detection.…”
Section: High-performance Liquid Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…Postmortem neurochemical analyses using high-performance liquid chromatography (HPLC) were performed as previously described (Enard et al, 2009;Winter et al, 2009). The levels of monoamines dopamine (DA) and serotonin (5-HT) and their metabolites dihydroxyphenylacetic acid (DOPAC), homovanillic acid (HVA), and 5-hydroxyindoleacetic acid (5-HIAA) in various brain areas were measured by HPLC with electrochemical detection.…”
Section: High-performance Liquid Chromatographymentioning
confidence: 99%
“…Interestingly, maturation of the different dopaminergic systems follows distinct developmental progression with differential temporal windows (Sturrock, 1980;Voorn et al, 1988), and wiring of dopaminergic projection systems appears to be extremely susceptible to neurodevelopmental insults. Various genetic as well as environmental manipulations, even when they are not directly targeting the dopaminergic systems, can lead to profound and specific longterm disturbances within distinct dopaminergic circuits (Roffler-Tarlov and Graybiel, 1984;Lipska et al, 2003;Fone and Porkess, 2008;Meyer et al, 2008;Winter et al, 2009 , 2007). Aberrant neuronal development in cortical and subcortical areas due to the lack of neuronal Nogo-A might therefore contribute to the development of the behavioral and neurochemical changes described here, as seen in schizophrenia (Weinberger, 1987;Harrison, 1999;Ross et al, 2006) and several neurodevelopmental models of this disease in animals (e.g., Shen et al, 2008).…”
Section: Nogo-amentioning
confidence: 99%
“…Moreover, it supports our recent hypothesis that a decrease in striatal serotonin and/or dopamine provides a final common pathway by which different brain pathologies lead to a pro-compulsive state. This hypothesis has been raised on the basis of the observation that similarly to lesions to the OFC, lesions to the subthalamic nucleus increase compulsive lever-pressing and decrease dopamine and serotonin (but not glutamate and GABA) in the striatum (Winter et al, 2008a). It is also noteworthy that pharmacological inactivation and high-frequency stimulation of the subthalamic nucleus, that exert an anticompulsive effect in the signal attenuation model (Klavir et al, 2009), have been reported to increase dopamine levels in the striatum (Bruet et al, 2001;Meissner et al, 2001;Lee et al, 2006).…”
Section: Ofc Lesionmentioning
confidence: 99%
“…There is strong evidence to support the notion that disturbances in neural developmental processes in utero caused by prenatal exposure to immunogens are a risk factor for the development of various psychopathologies such as schizophrenia (Brown et al, 2004;Mednick et al, 1988;O'Callaghan et al, 1994), attention deficit/hyperactivity disorder (Vuillermot et al, 2012), depression (Ling et al, 2004;Winter et al, 2009) and autism (Miller et al, 2005;Rodier and Hyman, 1998). In fact, both human and animal studies of prenatal immune activation have revealed abnormalities in adult brain cytoarchitecture, such as reduced dendritic arborization and abnormal neuronal migration (Deutsch et al, 2010;Fatemi and Folsom, 2009), suggesting a neurodevelopmental origin for some psychiatric illnesses that takes place prior to the onset of symptoms.…”
Section: Introductionmentioning
confidence: 99%